Ethnicity and Values - Льюис , Дэвид С. (Respublica literaria, 2021)
Cultures change in many ways but some basic values within the culture tend to remain over longer periods. Compared with some other potential markers of ethnicity, which may apply to only a certain part of an ethnic group, some traditional values are adhered to by most or perhaps even all members of the ethnic group. Over time, many core values of a culture remain relatively strong even though the manifestations of those values might gradually change. As such, certain cultural values can be regarded as stronger markers of ethnic or cultural identity than some other features of the culture which are more transient.